Antibacterial Properties of Organosulfur Compounds of Garlic (Allium sativum) - Bhatwalkar, Sushma Bagde; Mondal, Rajesh; Krishna, Suresh Babu Naidu; Adam, Jamila Khatoon; Govender, Patrick; Anupam, Rajaneesh (Frontiers in Microbiology, 2021)
Garlic (Allium sativum) a popular food spice and flavoring agent, has also been used traditionally to treat various ailments especially bacterial infections for centuries in various cultures around the world. The principle phytochemicals that exhibit antibacterial activity are oil soluble organosulphur compounds that include allicin, ajoenes and allyl sulphides. The organosulphur compounds of garlic exhibit a range of antibacterial activities such as bactericidal, anti-biofilm, anti-toxin and anti-quorum sensing (QS) against a wide range of bacteria including multi drug resistant strains. The reactive organosulphur compounds form disulphide bonds with free sulfhydryl groups of enzymes and compromise the integrity of bacterial membrane. World health organization (WHO) has recognized development of antibiotic resistance a global health concern and emphasizes antibiotic stewardship along with urgent need to develop novel antibiotics. Multiple antibacterial effects of organosulphur compounds provide an excellent framework to develop them into novel antibiotics. The review provides a focused and comprehensive portrait of status of garlic and its compounds as antibacterial agents. In addition, the emerging role new technologies to harness the potential of garlic as a novel antibacterial agent is discussed.